Direct determination of K B, Q, Q0 for cylindrical ionization chambers in a 6 MV 0.35 T MR-linac - Krauss, Achim; Renkamp, Claudia Katharina; Klüter, Sebastian (Physics in medicine and biology, 2020)
To ensure accurate reference dosimetry with ionization chambers in magnetic resonance linear accelerators (MR-linacs), the influence of the magnetic field on the response of the ionization chambers must be considered. The most direct method considering the influence of magnetic fields in dosimetry is to apply an appropriate absorbed-dose-to-water primary standard. At PTB, a new water calorimeter has been designed which is capable to determine Dw,Q in an MR-linac. The new device allows the direct calibration of ionization chambers in terms of absorbed dose to water for MR-linac irradiation conditions. Hence, the correction factors can be determined which replace the current radiation-quality dependent correction factors for dosimetry in the presence of magnetic fields. In cooperation with Heidelberg University Hospital, factors were measured at the 6 MV 0.35 T Viewray MR-linac for different cylindrical ionization chambers with sensitive volumes ranging from 0.015 cm3 to 0.65 cm3. The chambers were placed both perpendicular and parallel in respect to the magnetic field. Standard uncertainties of about 0.5% were achieved.
Im Titel sind B, Q, Q0 tiefgestellt
Gesehen am 27.01.2021